Global trends and disparities in the burden of heart failure caused by chronic kidney disease: an analysis of the global burden of disease study 2021 - Ye, Lingxia; Huang, Xin; Xu, Yufeng (Frontiers in Medicine, 2025)
BackgroundHeart failure (HF) is a major public health concern, and chronic kidney disease (CKD) plays a significant role in its pathogenesis. Understanding the trends and disparities in the burden of HF caused by CKD can provide valuable insights into health policymaking.MethodsThis study was a secondary analysis based on previously published data. We obtained global, regional, national, and age- and sex-specific data on the prevalence and years lived with disability (YLDs) of HF caused by CKD from the Global Burden of Disease Study 2021 (GBD 2021) and performed a secondary comparative analysis by age, sex, time, location, sociodemographic index (SDI), and health system level.ResultsIn 2021, there were 1,936.9 (95%UI: 1,600.2–2,343.5) thousand cases of HF caused by CKD globally, with an age-standardized rate of YLDs of 3.1 (95%UI: 1.9–4.4) per 100,000 population. The global burden of HF caused by CKD has continuously increased from 1990 to 2021 and is expected to keep growing through 2045 according to predictions. Significant disparities were found across different locations, genders, and ages. Higher burdens were noted among males, older individuals, and regions with lower SDI or less advanced health systems.ConclusionThe burden of HF caused by CKD has increased significantly since 1990 and varies widely across regions. More significant efforts are needed in the prevention and treatment of CKD and HF, especially among older individuals and males in regions with lower SDI or less advanced health systems.